Comparing a trauma focused and non trauma focused intervention with war affected Congolese youth: a preliminary randomised trial. Issue 1 (March 2015) - O'Callaghan, Paul; McMullen, John; Shannon, Ciarán; Rafferty, Harry
Abstract : While there is broad consensus about the need for interventions to help psychologically distressed, war affected youth, there is also limited research and even less agreement on which interventions work best. Therefore, this paper presents a randomised trial of trauma focused, and non trauma focused, interventions with war affected Congolese youth. Fifty war affected Congolese youth, who had been exposed to multiple adverse life events, were randomly assigned to either a Trauma Focused Cognitive Behavioural Therapy group or a non trauma based psychosocial intervention (Child Friendly Spaces). Non clinically trained, Congolese facilitators ran both groups. A convenience sample, waiting list group was also formed. Using blind assessors, participants were individually interviewed at pre intervention, post intervention and a 6-month follow-up using self-report posttraumatic stress and internalising symptoms, conduct problems and pro social behaviour. Both treatment groups made statistically significant improvements, compared to the control group. Large, within subject, effect sizes were reported at both post intervention and follow-up. At the 6-month follow-up, only the Child Friendly Spaces group showed a significant decrease in pro social behaviour. The paper concludes that both trauma focused and non trauma focused interventions led to reductions in psychological distress in war affected youth.